Pengaruh Teknik Audit Berbantuan Komputer, Kompetensi Auditor dan Audit Tenure terhadap Kualitas Audit : (Studi Empiris pada Kantor Akuntan Publik di Wilayah Jakarta Pusat) - Egi Endah Hanayanti; Veronica Setiawan (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This research was conducted with the aim of testing and analyzing the influence of computer-assisted audit techniques, auditor competency and audit tenure on audit quality. The population in this study were auditors who worked at Public Accounting Firms in the Central Jakarta Region. The type of research used in this research is quantitative research with data sources originating from primary data. The number of samples that meet the criteria is 101 samples. Sample selection was carried out based on the willingness of respondents who met the specified criteria and were willing to participate in this research. The research method used in this research was designed through research steps starting from operational variables, determining the type and source of data, data collection methods, research models and ending by designing data analysis and hypothesis testing with the help of SPSS 27 software as an analysis tool. After testing, it was found that computer-assisted audit techniques, auditor competency and audit tenure had a positive and significant effect on audit quality.